Analysis of Leading Sector Basic Sectors and Economic Sector Shifts in the Mamminasata Area - Rahman, Zainuddin (Journal of Social Research, 2023)
Economic growth is a crucial and strategic issue in regional and regional development planning. Economic growth is a central issue in regional and regional development, as stated in the Development Nawacita in the United Indonesian government under the leadership of Jokowi and Jusuf Kalla. In the concept of Nawacita, National development is oriented towards the development of villages to achieve equity and balanced regional growth. Nevertheless, a study is needed to find out which economic sectors are superior in the Mamminasata region, considering that the economic sectors in several regions do not yet have competitive advantages. Based on the phenomena faced by the regional government, this study chooses to examine the “Basic Leading Sector Analysis and Economic Sector Shifts in the Mamminasata Region by using descriptive quantitative and qualitative methods. The purpose of this study is to examine the leading sectors of regional development and economic growth (Maminasata) and explain regional development strategies and policies in South Sulawesi. The results of the study show that there are regencies and cities in the Mamminasata Region that have only three leading sectors and Makassar City has 15 leading sectors, which in general have regional competitiveness for themselves and the region or the province of South Sulawesi. In general, the economic sector in the region has low competitiveness and a constant rate of economic growth.